43.3k views
17 votes
Hello i would like help and the answer to this please; what is the nth term rule of

-5 -4 -1 4 1 1 20 31

1 Answer

4 votes

Answer:

The nth term of the given sequence


a_(n) = a_(n-1) + (2n-1)

Explanation:

Explanation:-

Given sequence -5,-4,-1,4,11,20,31

a₀ = -5

a₁ = a₀ +1 = -5 +1 = -4

a₂ = a₁ + 3 = -4+3 = -1

a₃ = a₂ + 5 = -1 +5 = 4

a₄ = a₃ + 7 = 4 + 7 =11

a₅ = a₄ + 9 = 11+9 = 20

a₆ = a₅ + 11 = 20+11 = 31

a₇ = a₆ + 13 = 31 +13 =44

and so on

The nth term of the given sequence


a_(n) = a_(n-1) + (2n-1)

User Raghu Chahar
by
5.0k points